PEMBERDAYAAN MASYARAKAT TENTANG PENTINGNYA PENDIDIKAN KARAKTER DI DESA PAMAROH KECAMATAN KADUR KABUPATEN PAMEKASAN - Sa’diyah, Halimatus; Fatah, Zainol; Aulia, Muzdalifah; Azizah, Delilia; Suci, Alfia; Noviandini, Anggi; Rahman, Anita (CV. Jendela Gagasan, 2025)
Community empowerment is now increasingly recognized as an alternative approach in the development process, as reflected in various literature and thoughts, including in efforts to strengthen the character of communities in rural areas. Character education plays an important role in bringing people to understand values cognitively, appreciate values emotionally (affectively), and apply these values in real life. The service activity was carried out in Pamaroh Kadur village Pamekasan which aimed to increase the capacity of the community in the aspect of character, especially in forming an attitude of responsibility. The methods used include Participatory Action Research (PAR) and literature review. PAR is a research approach that links the research process with social change efforts that actively involve researchers in their implementation. The data used consisted of primary and secondary data as support for the analysis. Through this activity, two main programs were designed. First, active involvement in activities that have been running in the community as a means to attract citizen participation. Second, the implementation of educational seminars is an effort to provide understanding to the public about the importance of education. The results of these two programs show an increase in attitudes of responsibility in children and adolescents in rural environments.